Use of Artificial Intelligence for Healthcare Purposes: A Structured Review - Sharma, Ashok; Singh, Parveen (International Journal of Computer Sciences and Engineering, 2022)
Artificial intelligence, which is widely defined as a machine's ability to mimic intelligent human behaviour, includes the subfield of machine learning. Artificial intelligence systems are employed to carry out difficult jobs in a manner a kin to how people solve problems. Data mining is a method of automatically discovering information from massive databases or data sets. Data mining is a technique for locating the information that is concealed in a large, challenging-to-access database using only standard queries. Additionally, machine learning demonstrates its close ties to data mining. Making software that teaches computers to get smarter as they encounter new data is the core objective of machine learning. Prediction systems, image identification, Speech recognition, medical diagnosis and other applications employ machine learning. Numerous areas, including research, engineering, health care, and business, produce and a vast volumes of data every day. In this study, a few data mining approaches, algorithms, and applications are discussed. Also, application of artificial intelligence in the field of healthcare industry such as Oral Pre-Cancerous Lesions and Oral Cancer Detection, Neurodegenerative disorders, Medical Disorders, Drug Discovery are discussed.